FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEMANDIRIAN PETANI DALAM PENGAMBILAN KEPUTUSAN USAHATANI DI KSM JAYA AMANAH, KABUPATEN BANDUNG - Dhyna Dellaura Pujakesuma; Tuti Karyani (Universitas Galuh Ciamis, 2020)
Indonesian agriculture is not free from capital problems so farmers still depend on moneylenders, middlemen, and government assistance. Islamic financing implemented by KSM Jaya Amanah by utilizing ZISWAF funds is aimed to empowering the community so it will improve the attitudes and behavior of each individuals and groups to become independent. This study aims to analyze the factors related to the independence of farmers in farm decision making. This research used quantitative research design with a census techniques. The method that is used for data analysis is descriptive statistical analysis and Spearman’s Rank test. The results showed that the independency of farmers of KSM Jaya Amanah in farm decision making is classified as moderate. The factors related to the independence of farmers in farm decision making are age, sex, farming experience, information’s availability and availability of facilities and infrastructure.